Efficiency Enhancement of Nanoporous Silicon/Polycrystalline-Silicon Solar Cells by Application of Trenched Electrodes - Kuen-Hsien Wu; Chia-Chun Tang (International Journal of Photoenergy)
Trenched electrodes were proposed to enhance the short-circuit current and conversion efficiency of polycrystalline-silicon (poly-Si) solar cells with nanoporous silicon (NPS) surface layers. NPS films that served as textured surface layers were firstly prepared on heavily doped p+-type (100) poly-Si wafers by anodic etching process. Interdigitated trenches were formed in the NPS layers by a reactive-ion-etch (RIE) process and Cr/Al double-layered metal was then deposited to fill the trenches and construct trenched-electrode-contacts (TEC’s). Cells with TEC structures (called “TEC cells”) obtained 5.5 times higher short-circuit current than that of cells with planar electrode contacts (called “non-TEC cells”). Most significantly, a TEC cell achieved 8 times higher conversion efficiency than that of a non-TEC cell. The enhanced short-circuit current and conversion efficiency in TEC cells were ascribed to the reduced overall series resistance of devices. In a TEC cell, trenched electrodes provided photocurrent flowing routes that directly access the poly-Si substrates without passing through the high resistive NPS layers. Therefore, the application of NPS surface layers with trenched electrodes is a novel approach to development of highly efficient poly-Si solar cells.